A cura di: Gianni Sammito

Calcolare

 

$lim_{x to -infty} (frac{2x+3}{2x})^{1-x}$

 


Il limite proposto equivale a

 

 

$lim_{x to -infty} (1 + frac{3}{2x})^{1-x}$

 

Ponendo

 

$frac{3}{2x} = frac{1}{t} implies x= frac{3}{2}t$

 

si ottiene

 

$lim_{t to -infty} (1 + frac{1}{t})^{1 – frac{3}{2}t} = lim_{t to -infty} (1 + frac{1}{t}) [(1 + frac{1}{t})^t]^{-frac{3}{2}} = 1 cdot e^{-frac{3}{2}} = e^{-frac{3}{2}}$

 

dove è stato sfruttato il limite notevole

 

$lim_{u to pm infty} (1 + frac{1}{u})^u = e$

 

FINE